2010
DOI: 10.1111/j.1474-9726.2009.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation pattern changes upon long‐term culture and aging of human mesenchymal stromal cells

Abstract: Within 2–3 months of in vitro culture-expansion, mesenchymal stromal cells (MSC) undergo replicative senescence characterized by cell enlargement, loss of differentiation potential and ultimate growth arrest. In this study, we have analyzed DNA methylation changes upon long-term culture of MSC by using the HumanMethylation27 BeadChip microarray assessing 27 578 unique CpG sites. Furthermore, we have compared MSC from young and elderly donors. Overall, methylation patterns were maintained throughout both long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
341
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(359 citation statements)
references
References 51 publications
16
341
1
1
Order By: Relevance
“…To investigate the intrinsic molecular changes upon NSPC aging, we report here a comprehensive set of transcriptional and epigenetic maps in young adult and aged SVZ NSPCs. We found that the NSPC epigenome was largely unchanged upon aging, which is broadly consistent with prior studies that profiled somatic stem cells from other aged tissues (Beerman et al., 2013; Bocker et al., 2011; Bork et al., 2010; Fernandez et al., 2015; Liu et al., 2013; Sun et al., 2014). In contrast to previous reports, we did not detect an age‐associated broadening of H3K4me3 (as in blood stem cells; Sun et al., 2014) and H3K27me3 (as in muscle satellite stem cells; Liu et al., 2013) domains in NSPCs, nor a global acquisition in DNA methylation levels (as in blood stem cells; Beerman et al., 2013; Sun et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the intrinsic molecular changes upon NSPC aging, we report here a comprehensive set of transcriptional and epigenetic maps in young adult and aged SVZ NSPCs. We found that the NSPC epigenome was largely unchanged upon aging, which is broadly consistent with prior studies that profiled somatic stem cells from other aged tissues (Beerman et al., 2013; Bocker et al., 2011; Bork et al., 2010; Fernandez et al., 2015; Liu et al., 2013; Sun et al., 2014). In contrast to previous reports, we did not detect an age‐associated broadening of H3K4me3 (as in blood stem cells; Sun et al., 2014) and H3K27me3 (as in muscle satellite stem cells; Liu et al., 2013) domains in NSPCs, nor a global acquisition in DNA methylation levels (as in blood stem cells; Beerman et al., 2013; Sun et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the epigenomes of three stem cell populations have been examined upon mouse and human aging: blood stem cells, mesenchymal stem cells and muscle satellite cells (Beerman et al., 2013; Bocker et al., 2011; Bork et al., 2010; Fernandez et al., 2015; Liu et al., 2013; Sun et al., 2014). Together, these studies conclude that the stem cell epigenome is relatively stable during aging, with a small number of potentially important loci that are significantly altered (Beerman & Rossi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cells, from which DNA was extracted for the CAU population, was immortalised 6-32 years before YRI cells (personal communication with Coriell). Though cryopreservation of animal cells is not thought to influence methylation, repeated growth and serial passaging of cells may [33] and the role of this phenomenon in observed differences can not be excluded. Our results suggest that ethnically diverse populations, at least when comparing YRI and CAU lymphoblastoid cell lines, may not only differ genetically in the VDR but also at an epigenetic level.…”
Section: Discussionmentioning
confidence: 99%
“…These cells, initially named fibroblast colony forming cells, differentiate into fibroblasts, adipocytes, chondrocytes, and osteocytes and were later renamed as MSC by Caplan and coworkers [35]. Genome-wide transcriptome and promoter methylation studies have shown that the expressed gene profile changes on culturing MSC in vitro with increased expression of, among others, cytoskeleton proteins and downregulation of cell cycle inhibitory genes [36], which is accompanied by progressive epigenetic changes [37]. There is also evidence that relatively minor changes to the culture conditions used to expand MSC, including culture at different oxygen tensions, use of fetal calf serum versus autologous serum, use of platelet lysate, or addition of growth factors (e.g., FGF2 or platelet-derived growth factor [PDGF]), affect MSC proliferation ability as well as the rate and degree of differentiation to the osteogenic, adipogenic, and chondrogenic lineages [36,[38][39][40][41].…”
Section: Can In Vitro Culture Convert Germline Stem/progenitor Cells mentioning
confidence: 99%